Pold3 is required for genomic stability and telomere integrity in embryonic stem cells and meiosis. Issue 7 (13th February 2018) - Zhou, Zhongcheng; Wang, Lingling; Ge, Feixiang; Gong, Peng; Wang, Hua; Wang, Feng; Chen, Lingyi; Liu, Lin
Abstract: Embryonic stem cells (ESCs) and meiosis are featured by relatively higher frequent homologous recombination associated with DNA double strand breaks (DSB) repair. Here, we show that Pold3 plays important roles in DSB repair, telomere maintenance and genomic stability of both ESCs and spermatocytes in mice. By attempting to generate Pold3 deficient mice using CRISPR/Cas9 or transcription activator-like effector nucleases, we show that complete loss of Pold3 ( Pold3 −/− ) resulted in early embryonic lethality at E6.5. Rapid DNA damage response and massive apoptosis occurred in both outgrowths of Pold3 -null ( Pold3 −/− ) blastocysts and Pold3 inducible knockout (iKO) ESCs. While Pold3 −/− ESCs were not achievable, Pold3 iKO led to increased DNA damage response, telomere loss and chromosome breaks accompanied by extended S phase. Meanwhile, loss of Pold3 resulted in replicative stress, micronucleation and aneuploidy. Also, DNA repair was impaired in Pold 3 +/− or Pold3 knockdown ESCs. Moreover, Pold3 mediates DNA replication and repair by regulating 53BP1, RIF1, ATR and ATM pathways. Furthermore, spermatocytes of Pold3 haploinsufficient ( Pold3 +/− ) mice with increasing age displayed impaired DSB repair, telomere shortening and loss, and chromosome breaks, like Pold3 iKO ESCs. These data suggest that Pold3 maintains telomere integrity and genomic stability of both ESCs and meiosis by suppressing replicative stress.